Toward an understanding of the DNA replication initiation in bacteria - Wegrzyn, Katarzyna; Konieczny, Igor (Frontiers in Microbiology, 2024)
Although the mechanism of DNA replication initiation has been investigated for over 50 years, many important discoveries have been made related to this process in recent years. In this mini-review, we discuss the current state of knowledge concerning the structure of the origin region in bacterial chromosomes and plasmids, recently discovered motifs recognized by replication initiator proteins and proposed in the literature models describing initial origin opening. We review structures of nucleoprotein complexes formed by replication initiators at chromosomal and plasmid replication origins and discuss their functional implications. We also discuss future research challenges in this field.